Entre matrice territoriale et enjeux sectoriels - Xabier Itçaina (Revue de la Régulation)
The article revisits the question of the territorial anchoring of cooperatives through an analytical framework that combines the regulationist approach and the sociology of political work. This general framing is put to the test through a case study of production cooperatives in the French Basque Country, considered as a social and economic movement aspiring to rebuild local development on a cooperative, territorial, and intersectoral basis. The visions of territorial development thus conveyed, however, are not static. Therefore, the article follows a socio-historical reading by distinguishing three sequences. The genesis of the movement, first, in the 1970s is characterized by its politicization since the founders of the SCOPs refer to a model of endogenous economic development, to the cross-border model of Mondragón, to territorial identity, and to inherited forms of cooperation. In a second phase, the movement slowed down due to some significant entrepreneurial failures in the 1980s and 1990s. Sectoral and market constraints put the cooperative model and inter-cooperation to the test. A third phase, starting in the 2000s, saw a redeployment of cooperatives within the framework of a broader spectrum of citizen mobilizations around the social and solidarity economy, but also around the ecological transition and the Basque language and culture, this redeployment coinciding with a substantial change in territorial governance. The concluding section looks at some general lessons on the territorial anchoring of cooperatives.